OPPORTUNISTIC INFECTIONS IN THE CONTEXT OF AIDS: A CLINICAL CASE (Web of Teachers: Inderscience Research, 2025)
Opportunistic infections (OIs) are the leading cause of morbidity and mortality in patients with acquired immunodeficiency syndrome (AIDS). This article presents clinical cases of two patients with HIV infection in the AIDS stage: a 32-year-old man and a 28-year-old woman, who developed various OIs. Diagnostic approaches, treatment strategies, and prognosis are discussed. Methods of prevention, including chemoprophylaxis and vaccination, are also considered. Additionally, risk factors, comorbidities, and possible complications are analyzed.